OPERATIONAL ART theory and practice. - Vego, Milan N. (Routledge advances in defence studies., 2025)
This book describes and explains the theory of operational art - an intermediate field of theory and practice between tactics and strategy. This book is one of relatively few works in the English language on the theory of operational art. It deals predominantly with the theory of operational art as applied to preparing, planning and conducting a high-intensity conventional war. In contrast to other works, the book is written in broad terms, rather than focusing on national military culture and experience, which allows more flexibility in adjusting to new evidence. The book explains the theory of operational art in all three physical dimensions (land, sea, and air/space) and describes/analyses various aspects of operational art in general terms, using historical examples to facilitate the understanding of the theory. The case studies focus on examples of major campaigns and operations in both the more recent and distant history of warfare, including the current Ukraine-Russia war. This book will be of much interest to students of strategic studies, military history, defense studies, and International Relations, as well as military professionals.